African and Afro-Caribbean Repatriation, 1919-1922 Black Voices - Chapman, Jane L. (Springer International Publishing, 2018)
This book is the first attempt to analyse records of people of Afro-Caribbean origin who appealed against repatriation during the painful period after Britain's1919 race riots. Revealing personal letters and petitions from the West Indies, West Africa, and the U.K., Jane Chapman demonstrates that conflict adjustment involving individual voices needs to be highlighted. She asks, what was the human environment, the dilemmas and the racist compulsions making transnational experiences in the British Empire so poignant? Analysing both the opinions of civil servants on appellants' statements of hardship and requests for financial help, and the voices of the appellants themselves, this book aims to rediscover black people's hidden heritage. .